Spontaneous Ectopic Paraumbilical Variceal Bleeding in a Patient With Cirrhosis - Dolly Patel; Rucha Borkhetaria; Victoria Motz; Shandiz Shahbazi; Thomas R. Riley (Annals of Internal Medicine: Clinical Cases)
Ectopic variceal hemorrhage is a rare sequela of portal hypertension, accounting for 5% of variceal bleeding events. Although mortality rates are high for this condition, there is no established management protocol. We present a patient case of spontaneous external hemorrhage from an ectopic paraumbilical varicosity in the setting of portal hypertension secondary to decompensated alcoholic cirrhosis that was treated effectively with transjugular intrahepatic portosystemic shunt placement.